Kwame Alexander's free write : a poetry notebook - Alexander, Kwame (Sourcebooks Wonderland/Sesame Workshop, 2020)
Provides a writing journal with prompts to inspire creativity. Includes poems, stories, quotes, activities, and writing guides.